Anxiolytic-like effects of hochuekkito in lipopolysaccharide-treated mice involve interleukin-6 inhibition - Ushio, Soichiro; Wada, Yudai; Nakamura, Mizuki; Matsumoto, Daiki; Hoshika, Kota; Shiromizu, Shoya; Iwata, Naohiro; Esumi, Satoru; Kajizono, Makoto; Kitamura, Yoshihisa; Sendo, Toshiaki (Frontiers in Pharmacology, 2022)
Hochuekkito (HET) is a Kampo medicine used to treat postoperative and post-illness general malaise and decreased motivation. HET is known to regulate immunity and modulate inflammation. However, the precise mechanism and effects of HET on inflammation-induced central nervous system disorders remain unclear. This study aimed to assess the effect of HET on inflammation-induced anxiety-like behavior and the mechanism underlying anxiety-like behavior induced by lipopolysaccharide (LPS). Institute of Cancer Research mice were treated with LPS (300 μg/kg, intraperitoneally), a bacterial endotoxin, to induce systemic inflammation. The mice were administered HET (1.0 g/kg, orally) once a day for 2 weeks before LPS treatment. The light-dark box test and the hole-board test were performed 24 h after the LPS injection to evaluate the effects of HET on anxiety-like behaviors. Serum samples were obtained at 2, 5, and 24 h after LPS injection, and interleukin-6 (IL-6) levels in serum were measured. Human and mouse macrophage cells (THP-1 and RAW264.7 cells, respectively) were used to investigate the effect of HET on LPS-induced IL-6 secretion. The repeated administration of HET prevented anxiety-like behavior and decreased serum IL-6 levels in LPS-treated mice. HET significantly suppressed LPS-induced IL-6 secretion in RAW264.7 and THP-1 cells. Similarly, glycyrrhizin, one of the chemical constituents of HET, suppressed LPS-induced anxiety-like behaviors. Our study revealed that HET ameliorated LPS-induced anxiety-like behavior and inhibited IL-6 release in vivo and in vitro. Therefore, we postulate that HET may be useful against inflammation-induced anxiety-like behavior.